LITERATURE REVIEW ON THE USE OF AUDIO MEDIA IN IMPROVING THE QUALITY OF LEARNING - NABILA CHAIRUNNISA (Teaching and General Education Studies, 2026)
Learning media play an important role in improving the quality of the teaching and learning process because they help teachers deliver learning materials more clearly and effectively. One of the media that can be utilized in learning is audio media, which delivers information through sound elements. This study aims to analyze the use of audio media in improving the quality of learning through a literature review approach. The method used in this study is a literature study by examining various scientific sources such as journals, books, and previous research related to audio media in learning. The results of the review indicate that audio media have several advantages, including improving students’ listening skills, increasing learning motivation, and providing flexibility because they can be accessed through various technological devices. In addition, audio media have relatively low production costs and are easy to distribute. However, audio media also have limitations because they rely only on the sense of hearing and are less effective for materials that require visual explanations. Therefore, the use of audio media should be adjusted to learning objectives and material characteristics to optimize the quality of learning.   Keywords: audio media, learning media, learning quality, literature review